Highly efficient fullerene and non-fullerene based ternary organic solar cells incorporating a new tetrathiocin-cored semiconductor. Issue 8 (19th June 2019) - Krishnan Jagadamma, Lethy; Taylor, Rupert G. D.; Kanibolotsky, Alexander L.; Sajjad, Muhammad Tariq; Wright, Iain A.; Horton, Peter N.; Coles, Simon J.; Samuel, Ifor D. W.; Skabara, Peter J.
Abstract : A dual-chain structural motif provides a new promising material for ternary OPV devices. Abstract : A new dual-chain oligothiophene-based organic semiconductor, EH-5T-TTC, is presented. The molecule contains two conjugated chains linked by a fused tetrathiocin core. X-ray crystallography reveals a boat conformation within the 8-membered sulfur heterocycle core and extensive π–π and intermolecular sulfur–sulfur interactions in the bulk, leading to a 2-dimensional structure. This unusual molecule has been studied as a ternary component in organic solar cell blends containing the electron donorPTB7-Th and both fullerene (PC71 BM ) and non-fullerene acceptorsITIC andEH-IDTBR . By incorporatingEH-5T-TTC as a ternary component, the power conversion efficiency of the binary blends containing non-fullerene acceptor increases by 17% (from 7.8% to 9.2%) and by 85% for the binary blend with fullerene acceptor (from 3.3% to 6.3%). Detailed characterisation of the ternary blend systems implies that the ternary small moleculeEH-5T-TTC functions differently in polymer:fullerene and polymer:non-fullerene blends and has dual functions of morphology modification and complementary spectral absorption.